(untitled) (New York,London, 2003)
Schaum's A-Z handbooks make excellent complements to course textbooks and test preparation guides. Ideal for ambitious high school seniors--especially AP students--and college freshmen, they feature concise, thoroughly cross-referenced definitions of hundreds of key terms and phrases that help students quickly break through the jargon barrier. Clear explanations of key concepts, supplemented with lucid illustrations, help build mastery of theory and provide a ready reference to supplement class work.
Keywords: Mathematics,Toán học; Handbooks, manuals, etc.,Cẩm nang, Sách hướng dẫn, vv